ANÁLISE DOS ANTECEDENTES E CONSEQUENTES DA QUALIDADE DO RELACIONAMENTO EM INSTITUIÇÕES DE ENSINO SUPERIOR PÚBLICAS ESTADUAIS - Danielle Mantovani; Joseane Petenaci de Araújo; Paulo Henrique Muller Prado (Revista Gestão Universitária na América Latina, 2013)
The main goal of this study is to a nalyze the antecedents and consequents of relationship quality of the students of public university where they study. The antecedents are perceived quality services and equity. The consequent variable is analyzed the academic loyalty. The relationship qua lity proposed here includes three variables: satisfaction, trust and commitment. With a methodological quantitative non probabilistic, a survey was conducted with 684 students of the twentytwo courses in the three existing campuses that are part of a Stat e University. The hypotheses confirmed the positive and significant impact among the antecedent variables (Perceived Quality and Equity) on satisfaction. The resulting constructs were also significant. We also found that perceived quality seems to be the m ost effective antecedent of trust than of satisfaction. Moreover, satisfaction, trust and commitment positively impact student loyalty. These results contribute to identify to important issues that contribute for the student to be part of the university an d have a good relationship with it.